BATASAN TINDAKAN PELECEHAN MATA UANG YANG DIGUNAKAN SEBAGAI MAHAR BERDASARKAN PASAL 35 AYAT (1) UNDANG-UNDANG NOMOR 7 TAHUN 2011 TENTANG MATA UANG (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The central bank under the name Bank Indonesia has the goal of achieving and maintaining the stability of the Rupiah value contained in Article 7 paragraph (1) of Law No. 3 of 2004 on Changes to the Law of the Republic of Indonesia No. 23 of 1999 on Bank Indonesia stating that: “Bank Indonesia’s goal is to achieve and maintain Rupiah stability”. But from some functions it turns out that money is also used as a dowry in a marriege. In the use of money for the manufacture of dowry marriege is generally done by folded, stapled, even glued.This legal research is a normative legal study or so-called doctrinal law research, in this study the authors conducted research on legal principles by utilizing descriptive, because the authors describe how restrictions on acts of currency abuse are used under Law No. 7 of 2011 on currencies, as well as to find out if the use of currencies as dowry is prohibited under Article 35 Paragraph (1) of Law No. 7 of 2011 on currencies.The result of the study conducted by the authors is, first the implementation of clear rules against the restrictions on currency abuse, and it is expected that changes to the law will include clear rules against the use of currencies as dowry that should not be used because it will damage the value of the currency.In accordance with Bank Indonesia Regulations only accept money exchange if it happens accidentally, but many people who exchange the money to the bank say the money was accidentally tampered with, even though the money was deliberately tampered with (in the steples, cut, glued, to the hole). This action is included in the criminal act that has sanctions in accordance with Article 35 Paragraph 1 No. 7 of 2011 on Currency. It should be implemented countermeasures by making special rules in the law so that the public is not arbitrary in committing criminal acts.Keywords : restriction of action-currency abuse-Mahar